1982
DOI: 10.1128/jb.150.3.1008-1015.1982
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Chondroitin Sulfate byBacteroides thetaiotaomicronGrowing in Carbohydrate-Limited Continuous Culture

Abstract: When Bacteroides thetaiotaomicron, an obligate anaerobe from the human colonic flora, was grown in continuous culture with the mucopolysaccharide chondroitin sulfate as the limiting source of carbohydrate, growth yields ranged from 48 g of cell dry weight per mol of equivalent monosaccharide at a growth rate of 3.5 h per generation to 32 g per mol at a growth rate of 24 h per generation. The theoretical maximum growth yield (61 g of cell dry weight per mol of equivalent monosaccharide) was comparable to that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Paper chromatography of this low-molecular-weight material revealed that it did not consist of unsaturated disaccharides (i.e., products of digestion of chondroitin sulfate by chondroitin lyase) but consisted of a compound which ran more slowly than ADi-4S on the paper chromatogram. This oligomer comigrated with an oligomer which we found previously in the extracellular fluid from bacteria which were grown in continuous culture with chondroitin sulfate as the sole carbohydrate source (16).…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…Paper chromatography of this low-molecular-weight material revealed that it did not consist of unsaturated disaccharides (i.e., products of digestion of chondroitin sulfate by chondroitin lyase) but consisted of a compound which ran more slowly than ADi-4S on the paper chromatogram. This oligomer comigrated with an oligomer which we found previously in the extracellular fluid from bacteria which were grown in continuous culture with chondroitin sulfate as the sole carbohydrate source (16).…”
Section: Resultssupporting
confidence: 74%
“…To determine whether chondroitin lyase was being released from the cells during incubation, samples of the extracellular fluid were tested for lyase activity by incubating 0.2-mi portions with chondroitin sulfate A and monitoring the increase in absorbance at 235 nm (16). To check for cell lysis during incubation, extracellular fluid was also assayed to detect the cytoplasmic enzyme phosphoglucose isomerase (11).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although beta-glucanases break down linkages in beta-glucan, and alpha-L-arabinofuranosidases break down linkages in rhamnogalacturonan and arabinan, a polysaccharide substrate containing both linkages has not been described. In contrast with several Bacteroides species, which catabolize polysaccharides from both animal and plant sources, all identified pPUL substrates for P. copri isolates were from plant sources, and none were from animal sources (Martens et al, 2011;Salyers AA, 1982).…”
Section: Polysaccharide Utilization Predictionmentioning
confidence: 83%